Menggali Pemikiran Rahmah El Yunusiah dalam Pendidikan Islam - Mulyanto, Mulyanto; Az Zahrah, Fatimah; Muslimah, Fadhilah Wardatul (TSAQOFAH, 2025)
Rahmah El Yunusiah is a significant figure in the development of Islamic education in Indonesia, particularly in advocating for women's access to education. This article examines Rahmah El Yunusiah's ideas, which emphasize the importance of education rooted in Islamic and moral values, as well as the integration of religious and general knowledge. Using a qualitative descriptive approach, the article analyzes Rahmah's contributions to the establishment of Madrasah Diniyah Putri, her impact on women's educational movements, and the relevance of her ideas in addressing modern educational challenges. The findings show that Rahmah's intellectual legacy remains relevant in creating an inclusive and equitable education system, contributing to the empowerment of women in society.